On the Base of Molecular Data, A Great Difference Between Sedentary Subspecies of Prinia Subflava Gmelin, 1789 Suggests Resurrecting Name Prinia Mutatrix Meise, 1936 - Nguembock, Billy; Sali, Mahamat; Diane Olivia, Azang Esther; Yollande, Guehoada (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Prinia subflava is a sedentary member of the “open warblers cisticolid” clade and in our first papers, it appeared with a strong divergence between Prinia subflava subflava and Prinia subflava mutatrix. To confirm this divergence and leaning partially on our first obtained results, we investigated a genetic variation of the individuals of P. s. subflava (Western Africa) and P. s. mutatrix (Southeastern Africa). For the genetic variation, we used three mitochondrial genes (ATPase6, ND2 and ND3) to calculate their genetic distances within the cisticolid ingroup and to explore their mutational differentiation. With our ATPase6, ND2 and ND3, a genetic distance of 5.76%, 5.15% and 5.13% has been estimated respectively between individuals of P. s. subflava (Cameroon) and P. s. mutatrix (Malawi) whereas it was, for the proteincoding gene ND2, only of 1.81% between specimens of P. s. subflava caught in Western Africa parts (Gambia and Cameroon). For the mutational differentiation, a total of 113 different molecular characters have been observed on the three markers investigated between P. s. subflava and P. s. mutatrix. Otherwise leaning on our dating results, Prinia subflava subflava diverged from Prinia subflava mutatrix during the Pliocene epoch. It is known that the East African Rift system of which the western branch formed the giant arc from Uganda to Malawi began its formation after a large uplift of East Africa during the Oligocene Epoch followed by climatic fluctuations in Africa with the global cooling during the Neogene period. Thus for these sedentary birds separated of around 3162 km with several geographic barriers and for which no risk of recurrent gene flow is possible, we suggest resur